2000
DOI: 10.1148/radiology.214.1.r00ja04127
|View full text |Cite
|
Sign up to set email alerts
|

Postcatheterization Pseudoaneurysms and Arteriovenous Fistulas: Repair withPercutaneous Implantation of Endovascular Covered Stents

Abstract: Implantation of endovascular covered stents is an effective and safe method for the percutaneous closure of pseudoaneurysms and arteriovenous fistulas. Thus, endoluminal vascular repair with covered stents offers an alternative therapeutic approach to vascular surgery in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
113
0
27

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(141 citation statements)
references
References 39 publications
(18 reference statements)
1
113
0
27
Order By: Relevance
“…Although a minimally invasive surgical repair should be considered as the first choice in treatment for pseudoaneurysms, implantation of endovascular covered stents could also be another option to be considered. A previous study reported the feasibility and acceptability of endoluminal vascular repair with covered stents in selected patients [12]. On the other hand, the covered stent could provide disadvantages for younger patients with a long life expectancy, because the long-term consequences of implanting covered stents are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although a minimally invasive surgical repair should be considered as the first choice in treatment for pseudoaneurysms, implantation of endovascular covered stents could also be another option to be considered. A previous study reported the feasibility and acceptability of endoluminal vascular repair with covered stents in selected patients [12]. On the other hand, the covered stent could provide disadvantages for younger patients with a long life expectancy, because the long-term consequences of implanting covered stents are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Percutaneous closure with stent grafts for cases with unsuccessful ultrasonic compression repair is an attractive, safe, effective alternative to conventional surgery. 15,16 Short-term follow-up is encouraging, however, long-term follow-up of these procedures is warranted to assess durability of the repair and absence of complications. 17 Recently, an experimental study was done on a rat groin flap model to assess the possible effects of arteriovenous fistulas on the viability of skin flaps.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5 Psö do a nev riz ma la rın ço ğu spontan ola rak trom bo ze olup ka pa nır ken, ka pan ma yan yak la şık %10-20 va ka te da vi ge rek ti rir. 7,8 Psö do a nev riz ma la rın te da vi yön tem le ri arasın da Dopp ler ul tra so nog ra fi eş li ğin de kom presyon, Dopp ler ul tra so nog ra fi eş li ğin de trom bin en jek si yo nu, en do vas kü ler em bo li zas yon ve stentgreft le me, cer ra hi yön tem ler (li gas yon, re zek si yon ve greft le me) sa yı la bi lir.…”
Section: Tar Tiş Maunclassified
“…Lo kal anes te zi ile uy gu lan ma sı, has ta ne de ka lış sü-re si ni kı sa ol ma sı, komp li kas yon oran la rı nın açık cer ra hi ye gö re dü şük ol ma sı yön te min avan taj la rı -dır. 7,8,10 Post ka te te ri zas yon is ten me yen du rum la rı ne de ni ile te da vi edil me si ge re ken has ta la rın ço ğu -nun ile ri yaş ta, yay gın da mar has ta lı ğı ve sis te mik has ta lık la rı olan bir gru bu kap sa ma sı mi ni mal in vaziv gi ri şim le rin kul la nı mı nı ter cih edi lir kıl mak tadır.…”
Section: Tar Tiş Maunclassified
See 1 more Smart Citation